KANTOR GRID NETWORK KOMPAS GRAMEDIA JAKARTA PUSAT UPAYA NEXT NORMAL WORKLIFE STRATEGY - Halim, David; Nurfansyah, Nurfansyah (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
The ongoing Covid-19 pandemic has changed many things, working from home has also changed employees' point of views on safety in the workplace should they have to return to work from the office, similar to the Grid Network company which is a subsidiary of Kompas Gramedia for publications that produce and distribute the news, entertainment and lifestyle. Because the output from this media is digital and print, work from the office is still very necessary and cannot be completely replaced by an online system. This is realized by using spatial perception method with Biophillic concept, which is a form of sustainable building design that has great potential to contribute to human health and well-being, especially in the midst of a pandemic. This method not only contributes to the aesthetics and functionality of the space, but also helps in the process of creating a workspace that minimizes employees' exposure to the risk of Covid-19 transmission.